Female composers’ use of online communities of practice to build and support their careers - Hennekam, S.; Macarthur, S.; Bennett, Dawn; Hope, C.; Goh, T. (Emerald, 2019)
This article examines women composers’ use of online communities of practice to negotiate the traditionally masculine space of music composition while operating outside its hierarchical structures. We employed a mixed methods approach consisting of an online survey (n=225) followed by 27 semi-structured in-depth interviews with female composers to explore the concept and use of communities of practice. Content analysis was used to analyse the survey responses and interpretative phenomenological analysis was used to interpret respondents’ lived experiences as relayed in the interviews. The findings reveal that the online environment can be a supportive and safe space for female composers to connect with others and find support, feedback and mentorship, increase their visibility, and develop career agency through learning and knowledge acquisition. Communities of practice emerged as an alternative approach to career development for practicing female music workers and as a tool which could circumvent some of the enduring gendered challenges. The findings suggest that online communities of practice can have a positive impact on the career development and sustainability of women in male-dominated sectors such as composition.